2018
DOI: 10.9745/ghsp-d-18-00205
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Large-Scale Community-Based Contraceptive Distribution Program in Kinshasa, DRC Based on Process Evaluation

Abstract: Midterm process evaluation results indicated that design and implementation failures hindered the program's success, notably: (1) the short-acting methods provided by community-based distributors (CBDs) offered limited choice; (2) the nominal revenue retained from selling the methods provided limited motivation for the volunteer CBDs; and (3) the model was poorly coordinated with the existing clinical service system, partly because of challenging systems issues. In the revised model, the CBDs will also provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Investments in quality, combined with free care, can therefore improve equity. For short-acting method users, community-level provision may improve their access and use of contraception, although results from such pilots in DRC have thus far been mixed [26,27]. It is, however, important to note that 20-24-year-olds were more likely to receive contraceptive information from health workers or CHWs than 15-19-yearolds.…”
Section: Plos Medicinementioning
confidence: 99%
“…Investments in quality, combined with free care, can therefore improve equity. For short-acting method users, community-level provision may improve their access and use of contraception, although results from such pilots in DRC have thus far been mixed [26,27]. It is, however, important to note that 20-24-year-olds were more likely to receive contraceptive information from health workers or CHWs than 15-19-yearolds.…”
Section: Plos Medicinementioning
confidence: 99%
“…In this issue of GHSP, Hernandez and colleagues present a notable description of how their process evaluation of a large community-based distribution (CBD) program in the capital city of the Democratic Republic of the Congo (DRC), Kinshasa, led to major improvements in that program 1 . We compliment the authors for forthrightly detailing the weaknesses they observed in the original design of the AcQual program and the reasonable changes they subsequently have made.…”
mentioning
confidence: 96%
“…To overcome such challenges, increasing the number of the education sessions, arranging a group talk in a break and reassured the community names and personal information would be kept con dential by the promoters (40). Also, weak Interaction with clinical Services, having weak support and supervision of Community-Based Distributors and Recurring Stock-Outs of contraceptive (32). In line with these studies, our study deploys the following mechanism to minimize the challenges in the provision of the interventions.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in the Kinshasa study, they recruited community-based distributors (CBDs) to have a group discussion, individual counseling, distribution of contraceptive (condom, pills, and CycleBeads) and arranging referral (32). Besides, a study done in Bahir district of India reports that an increment of FP following provision of training to the rural provider and community leaders, group meeting, and disseminating message using street theatre and wall painting for a total provision of the intervention 21-27 months.…”
Section: Discussionmentioning
confidence: 99%